2021
DOI: 10.1111/jfpe.13640
|View full text |Cite
|
Sign up to set email alerts
|

Impact of variability in protein content of sunflower meal on the extrusion process and physical quality of the extruded salmonid feed

Abstract: Abstact This study aimed to characterize sunflower meal (SFM) with a protein content of ~370 g/kg per dry matter (SFM1) and its two high protein fractions obtained by air classification (SFM2 and SFM3 containing 430 and 490 g/kg of protein per dry matter, respectively) as aqua feed ingredient, based on their functional properties that are important for extrusion processing. A mixture design was applied, varying the levels of SFM1, SFM2 and SFM3 from 88.2 to 267.2 g/kg in dry feed mixes intended for trout. SFM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…However, when the CAP replacement level reached 100%, the oil leakage of feeds increased, which could be attributed to the high content of large pores. Banjac et al (2021) reported that oil leakage mainly occurred in the large pores.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the CAP replacement level reached 100%, the oil leakage of feeds increased, which could be attributed to the high content of large pores. Banjac et al (2021) reported that oil leakage mainly occurred in the large pores.…”
Section: Discussionmentioning
confidence: 99%
“…Fiber content of the formula seems to be one of the major components that may affect the physical parameters in the current study. Microstructure of high fiber-sunflower meal extrudates showed unevenly-sized large pores in the inside, while extrudates of low fiber-sunflower meal showed uniform pores and higher expansion ratio (Banjac et al, 2021). Supplementation of high cellulose level of 10% caused a cell size reduction of the extruded cassava starch since it might cause fiber accumulation and non-uniform distribution of fiber in the starch matrix (Kaisangsri et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…extrusion: grain, beans, fruits, vegetables, tubers, leaves and stems of plants, as well as their mixtures [1,2].…”
Section: Determination Of the Cellulose-and Lipid-containing Componen...mentioning
confidence: 99%